Effects of exchange rate volatility on outputs in some selected West Africa countries - Sani, Idris Ahmed; Hassan, Sallahuddin; Azam, Muhammad (European Centre for Research Training and Development UK, 2016)
This study investigates empirically the effect of exchange rate volatility on the output level of the five English speaking countries in ECOWAS, namely Nigeria, Ghana, Gambia, the Sierra Leones and Liberia, over the period 1991 to 2014.Co-integration test and error correction modelling were used as estimation techniques.Estimates of co-integration relations were obtained and the short-run and long-run dynamic relationships between the variables were obtained for each country utilizing the tests.In general, exchange rate volatility has a significant impact on outputs at least for all the countries considered in the study, with all except Liberia having negative impact.